Elevated Neopterin Levels Predict Fatal Outcome in SARS-CoV-2-Infected Patients - Chauvin, Manon; Larsen, Martin; Quirant, Bibiana; Quentric, Paul; Dorgham, Karim; Royer, Luca; Vallet, Hélène; Guihot, Amelie; Combadière, Béhazine; Combadière, Christophe; Barallat, Jaume; Mayaux, Julien; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Highlights Innate immune activation during Covid-19 infection is associated with pernicious clinical outcome. Background Coronavirus disease 2019 (Covid-19) is a worldwide threat that has already caused more than 3 000 000 deaths. It is characterized by different patterns of disease evolution depending on host factors among which old-age and pre-existing comorbidities play a detrimental role. Previous coronavirus epidemics, notably SARS-CoV, were associated with increased serum neopterin levels, which can be interpreted as a sign of acute innate immunity in response to viral infection. Here we hypothesize that neopterin may serve as a biomarker of SARS-CoV-2 viral infection and Covid-19 disease severity. Methods We measured neopterin blood levels by ELISA. Seric concentration was quantified from 256 healthy donors and 374 Covid-19 patients at hospital admission. Enrolled Covid-19 patients were all symptomatic and displayed a large spectrum of comorbidities. Patients were followed until disease resolution or death. Results Severe and critically ill SARS-CoV-2 infected patients were characterized by a profound exacerbation of immune activation characterized by elevated neopterin blood levels. Systemic neopterin levels above 19nM stratified healthy individuals from Covid-19 patients with 87% specificity and 100% sensitivity. Moreover, systemic neopterin levels above 53nM differentiated non-survivors from survivors with 64% specificity and 100% sensitivity. Conclusion We propose that neopterin concentration measured at arrival to hospital is a hallmark of severe Covid-19 and identifies a high-risk population of pernicious clinical outcome with a need for special medical care.